Analisis Pelatihan Terhadap Peningkatan Kinerja Karyawan Pada PT Mitra Asri Pratama Jakarta Selatan - Akbar, Ahmad; Imbron Imbron (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the implementation of training programs at PT Mitra Asri Pratama and evaluate their impact on the performance of cleaning service employees. The research is motivated by low performance achievement, particularly in 2023, when a performance gap of -17.2% occurred due to low training participation and limited evaluation. A descriptive qualitative method was applied, with data collected through semi-structured interviews, observations, and documentation. Data validity was ensured using source and technique triangulation. The findings reveal that training is conducted through initial induction and annual programs focusing on Service Excellence, ASK (Attitude, Skill, Knowledge), and Standard Operating Procedures (SOP). However, the effectiveness of these programs remains limited due to monotonous delivery methods and the absence of a comprehensive training needs analysis. Improvements made in 2024 resulted in moderate performance growth